Measurement of the deuterium flux in cosmic rays with the Alpha Magnetic Spectrometer on the International Space Station - Bueno, Eduardo Ferronato (2018)
This work presents the measurement of the deuterium flux, and the deuterium-to-hydrogen flux ratio from 0.6 to 10 GeV/n, using data collected between May 2011 and May 2015 by the Alpha Magnetic Spectrometer (AMS-02), a cosmic ray detector operating aboard the International Space Station (ISS) since May 2011. The isotope separation is performed by combining the measurements performed by the AMS-02 sub-detectors. In particular, the mass measurement is carried out by taking advantage of the precise momentum measurement provided by the silicon tracker and by the velocity measurement provided by the Cherenkov detector. The event counting method is performed using reference spectra of simulated signal and background events, where the agreement between data and Monte Carlo has been carefully checked and eventual differences have been mitigate by means of corrections based on the comparison between the resolution of the velocity and momentum as obtained from data and simulated vents. Production mechanisms, acceleration and propagation of cosmic rays are not completely clear, therefore precise measurements of the flux and composition of these particles may help to understand these phenomena. In the conventional model, supernova remnants are the sources of cosmic rays in the GeV to TeV energy range. The so called primaries, such as 1H, 4He, e- and C are believed to be produced and accelerated at the sources, while secondaries, such as e+, 2H, 3He and B originate from the collisions of primary cosmic rays with the interstellar medium. Hence, secondaries carry information about the propagation of cosmic rays in the galaxy, and, the measurement of their flux is used to constrain the parameters of cosmic ray propagation models; in particular, studying secondary-to-primary ratios is useful as it factors out the unknown source spectrum of the progenitor. One of such commonly studied ratios is the B/C ratio, but other ratios, such as 2H/1H and 3He/4He, can be used to probe a different A/Z regime and test the universality of the propagation mechanisms.